Menstrual dysfunction in women of reproductive age belonging to major ethnic groups in Eastern Siberia: a cross-sectional study - L. M. Lazareva; A. V. Atalyan; L. V. Belenkaya; I. N. Danusevich; Ya. G. Nadelyaeva; E. M. Sharifulin; I. Yu. Egorova; N. I. Babaeva; M. D. Salimova; L. V. Suturina (Фундаментальная и клиническая медицина, 2023)
Aim. To determine the prevalence and features of menstrual dysfunction in premenopausal women of various ethnicities inhabitating Eastern Siberia.Materials and Methods. We conducted a cross-sectional study which included women of reproductive age (18-44 years) living in the Irkutsk region and the Republic of Buryatia. Out of 1134 women, 715 (63.1%) were Caucasians, 312 (27.5%) were Asians (Mongoloid), and 107 (9.4%) were of mixed ethnicity. The data have been collected during the annual physical examination carried out between March 2016 to May 2021,Results. The average age of menarche onset was 13.3 ± 1.4 years and did not differ significantly in Caucasians, Asians, and group of mixed ethnicities. The most frequent ages for menarche were 11 and 15 years among women of mixed ethnicity and Asians, respectively. Chronic abnormal uterine bleeding and dysmenorrhea was detected in 573/1134 (50.5%) and in 280/1134 (24.7%) of the examined women, respectively, without significant differences between the ethnicities. However, dysmenorrhea symptoms were more severe in Caucasians as compared to Asian women.Conclusion. The most frequent variant of menstrual dysfunction is chronic abnormal uterine bleeding. There were no significant differences in the prevalence of irregular menstrual cycles, oligo/anovulation, chronic abnormal uterine bleeding, and dysmenorrhea in women of reproductive age belonging to different ethnicities, although clinical manifestations of dysmenorrhea were most pronounced in Caucasians.